Physical therapy for congenital muscular torticollis (Physical Culture and Sport: Scientific Perspective, 2024)
Congenital muscular torticollis (CMT) is one of the most common musculoskeletal diseases in children, characterized by fibrosis or shortening of the sternocleidomastoid muscle, which leads to lateral bending of the head to the affected side and rotation to the opposite side. The incidence rate of congenital torticollis worldwide ranges from 0.3% to 1.9%, according to other studies the ratio is 1 in 250 newborns, with a predominance of male infants born from first pregnancies.Early recognition of CMT symptoms and physical therapy is an important part of conservative treatment, considered effective in the majority of cases. The main goal of physical therapy (PT) is to achieve age-appropriate active and passive range of motion of the neck, prevent contractures, and develop symmetry of the face, head, and neck. Early intervention for a child with congenital torticollis, started before the age of 1 month, has a 98% success rate, with a duration of therapy of approximately 2.5 months, resulting in the infant achieving near-normal range of motion. The leading methods of physical therapy at an early age are passive muscle stretching, active muscle stretching, development of active symmetrical movements, adaptation of the environment, training of parents or guardians of the child in positioning skills and features of child care in everyday family life. An individual approach and high-quality selection of PT drugs are the key to obtaining good results, minimizing the possibility of negative consequences of the disease, and shortening the duration of treatment.The aim of the study is to review the literature, which highlights the issue of selection and application of physical therapy methods for infants with muscular torticollis, to determine the most effective ways to solve the problem.
Keywords: congenital muscular torticollis; treatment; physical therapy; early intervention; children